Structure, Function, and Therapeutic Potential of Marine Bioactive Peptides - Tatiana V. Ovchinnikova (Marine Drugs, 2019)
In recent years, bioactive peptides from marine organisms have gained increasing attention in the field of pharmaceutical, cosmeceutical, and nutraceutical product development owing to their interesting biological properties [...]